Cardiac resynchronization therapy in a case with single ventricle and concommitant noncompaction cardiomyopathy - Deniz Elçik; Mustafa Fehmi Bireciklioğlu; Ali Doğan; Mehmet Tuğrul İnanç (KARE Publishing, 2020)
A 32-year-old male patient was admitted to the hospital with syncope. An electrocardiogram revealed complete atrioventricular (AV) block and a right bundle branch block with a QRS duration of 218 milliseconds. The heart rate was 40 beats/minute. Echocardiography revealed that both AV valves opened to a single ventricle as well as noncompaction of the myocardium. Due to New York Heart Association class III heart failure, cardiac resynchronization therapy with a defibrillator device (CRT-D) was performed. After the implantation, the electrocardiography QRS duration was reduced to 183 ms. To our knowledge, this was the first reported case of CRT-D implantation in a patient with a noncompacted single ventricle and complete AV block.